Efektifitas RCEP dalam Mendorong Perdagangan di ASEAN - Muhamad Abdul Faiz; Ferdy Octaviano; Algi Muhammad Hustan (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2025)
Regional Comprehensive Economic Partnership (RCEP) is a free trade agreement involving 15 countries in the Asia-Pacific region, including 10 ASEAN member states as well as partners such as China, Japan, South Korea, Australia and New Zealand. Signed in November 2020, RCEP is one of the largest trade agreements in the world, covering around 30% of the global population and world GDP. For ASEAN countries, RCEP has important objectives, including improving market access, reducing tariffs and trade barriers, and strengthening economic integration. This agreement is expected to have a significant positive impact on the economy and trade in ASEAN, by driving economic growth through increased trade and investment, creating jobs, and improving people's welfare. In addition, RCEP also enables economic diversification by providing access to new markets, thus reducing dependence on traditional markets. By harmonizing standards and regulations, RCEP can increase the competitiveness of products from ASEAN countries in the global market, thus strengthening their position in the world economy.